PERUBAHAN SIFAT KIMIA TANAH GAMBUT SETELAH PEMBERIAN LIMBAH PABRIK KELAPA SAWIT (Changes of Chemical Properties of Peat Soil After Given Waste of Oil Palm Mill) - Y, Sulistiyanto; V., Amelia; millah, Ka; M. A., Rassid (Universitas Palangka Raya, 2015)
ABSCTRACTThe purpose of this study was to assess changes of chemical properties of peat after being given asewage of oil palm mill. The research was conducted from September to December 2014 atAnalytical Laboratory University of Palangkaraya. This research is a quantitative way of measuringand comparing the chemical properties of peat were given sewage of oil palm mill, such as, boiler ashof palm oil mill (AB), wastewater of palm oil mill (LC), and oil palm empty fruit bunches (TK). ABdose used was 11.6 tonnes / ha, LC 1.800 L / 12 M2, and TK 20 tonnes / ha. Parameters measuredwere pH, available P, K-dd, Ca-dd, Mg-dd. Soil pH observations carried out at 0 weeks of incubation(0 MSI), 4 MSI, 8 MSI, 12 MSI, and 16 MSI. As for the P-Available, Ca-dd, Mg-dd, and K-ddperformed at 0 MSI, 8 MSI, and 16 MSI. The results showed that treatment of AB on peat soil in 8MSI showed the highest increase in available P and giving LC on peat soil in 8 MSI showed anincrease in the value of the K-dd, Ca-dd, and Mg-dd.Keywords: boiler ash, wastewater, soil chemical properties; oil palm empty fruit bunches